Analysis of Murabahah Financing in Sharia Banking (Bank BJBS KCP Arcamanik Case Study) - Saiful Alfadz; Muhammad Al Mighwar (ORGANIZE: Journal of Economics, Management and Finance, 2024)
Murabahah is an agreement for the sale and purchase of an item where the seller states the selling price which consists of the cost price and a certain level of profit on the item where the selling price is agreed to by the buyer.  The purpose of writing this article is to analyze the issue of murabahah financing in sharia banking. This research examines the banking sector in Indonesia as the focus of the study, especially in terms of solving practical operational problems through exploratory investigations. Three customers and three sharia bank employees were tested in the study material in Bank BJBS KCP Arcamanik's sharia banking research. The Sharia Supervisory Board has carried out good supervision and must carry out strict supervision so that murabahah financing is carried out in accordance with this concept. This is so that murabahah financing which is the foundation for sharia banking financing can continue to exist and not damage the reputation or image of sharia banking.